Nonylphenol ethoxylates biodegradation increases estrogenicity of textile wastewater in biological treatment systems. (1st October 2020) - He, Xiwei; Qi, Zhaodong; Gao, Jie; Huang, Kailong; Li, Mei; Springael, Dirk; Zhang, Xu-Xiang
Abstract: The formation of estrogenic intermediates, i.e. nonylphenol diethoxylate (NP2EO), nonylphenol monoethoxylate (NP1EO), and nonylphenol (NP), following nonylphenol ethoxylates (NPEOs) biodegradation in textile wastewater raises concerns about its endocrine disruptive activity, but the estrogenicity changes of textile wastewater throughout biological treatment processes remain unknown. In the present study, the estrogenicity of textile wastewater sampled from 10 wastewater treatment plants (WWTPs) were investigated using the reporter gene-based T47D-KBluc bioassay. Results showed that the estrogenicity of the textile wastewater significantly increased after either anaerobic or aerobic treatment in all WWTPs, with an average fold change of 3.21, although traditional pollutants were effectively removed. The estradiol equivalents of the effluent (ranging from 1.50 to 4.12 ng-E2/L) were generally higher than published effect based trigger values, indicating an increased risk for the receiving waters. Removal efficiency was high (84.46%) for NPEOs, but was low for NP2EO and NP1EO in the biological treatment processes. Nevertheless, NP had increased concentrations after the treatment. Bioanalytical equivalent concentration of the textile wastewater and that of NP2EO, NP1EO, and NP showed a good linear correlation, of which NP alone contributed more than 70% to the observed estrogenicity. Extending hydraulic retention time was found effective in reducing the estrogenicity as it allows relatively complete degradation of NP, which was further confirmed by running lab-scale A/O reactors fed with NP10EO. The results may extend our knowledge regarding the estrogenicity of textile wastewater and its reduction technologies used in WWTPs. Highlights: Biological treatments increase estrogenicity of textile wastewater. NPEOs biodegradation contributes to the increase of estrogenicity. NP is the key toxicant for inducing the estrogenicity of textile wastewater. Extending HRT is effective in reducing the effluent estrogenicity.